Stradling a Cultural Doctrine: Exploring Historical Trauma on Ethnic Identity Development Among the Mestizo Peoples - (:unkn) unknown (My University, 2020)
ABSTRACT STRADDLING A CULTURAL DOCTRINE: EXPLORING HISTORICAL TRAUMA ON ETHNIC IDENTITY DEVELOPMENT AMONG MESTIZO PEOPLES by Esmeralda Gill The University of Wisconsin-Milwaukee, 2020 Under the Supervision of Professor Marty Sapp, Ed.D. The modern descendants from the territory now known as Mexico, the Mestizo, are known to primarily be an admixture of Indigenous and European ancestry. Mestizo ethnic nomenclature acknowledges the presence of Indigenous Peoples in an individual’s ethnic background. Though the Mestizo narrative is saturated in collective mass group trauma and chronic complex forms of racism, discrimination, and systemic oppressive forces that delineate from colonialism, the Mestizo are also known to be resilient. Consequently, it is prudent to evaluate the extent to which the legacy of colonization affects ethnic identity facets among the Mexican-origin populations as ethnic identity is known to greatly influence mental health wellness, as mental health services are underutilized by those originating from Mexico. Post-colonization brings myriad ethnic labels rooted in Eurocentrism. Contemporary ethnic labels affect how individuals understand themselves, how others perceive them, and how community members use this information to connect to one another. Given that Mestizo people ensued conquest, exploitation, and current Eurocentric influences, the applicability of historical trauma is essential to evaluate ethnic identity development among this population. Thus, this project involved the use of a historical trauma paradigm to understand ethnic identity formation among Mestizos in the hopes that results could be used to deepen the scope of culturally adaptive mental health services available to this population. This qualitative inquiry captured intergenerational historical trauma using the Trauma and the Continuity of Self: A Multidimensional, Multidisciplinary Integrative Framework. The Nigrescence model of ethnic identity was also used to explore ethnic identity experiences among participants. A total of nine self-identified Mestizo participants recruited for this project completed the Comprehensive History Questionnaire in conjunction with an in-person interview. Findings from this project indicate ethnic identity factors such as ethnic affirming college courses/organizations, community, family, pride, forms of resistance, and indigeneity helped foster a cohesive ethnic identity development. Conversely, navigating identity confusion and feeling like an outsider contributed to a disrupted sense of self. In addition, findings support that participants’ ethnic identity formation was disrupted by historical trauma-related constructs. This research inquiry offers insight into possible interventions to support healthy ethnic identity formation among Mexican-origin individuals.